2011
DOI: 10.1097/aap.0b013e3182176f5a
|View full text |Cite
|
Sign up to set email alerts
|

Transient Heat Hyperalgesia During Resolution of Ropivacaine Sciatic Nerve Block in the Rat

Abstract: Background Preliminary studies using perineural sciatic ropivacaine in rat demonstrated unexpected heat hyperalgesia after block resolution. To better characterize the time course relative to mechanical anesthesia-analgesia, we tested the hypothesis that ropivacaine 0.5% leads to transient heat hyperalgesia in rat independent of mechanical nociception. We also evaluated functional toxicity (e.g., long-term hyperalgesia and/or tactile allodynia 2 weeks post-injection). Methods Under surgical exposure, left sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 20 publications
2
24
1
2
Order By: Relevance
“…In this animal model, we also noticed a transient hypersensitivity to heat in the R group as previously described. 23 This hypersensitivity seemed to be corrected with perineural dexamethasone but not with systemic dexamethasone (Fig. 3).…”
Section: Discussionmentioning
confidence: 95%
“…In this animal model, we also noticed a transient hypersensitivity to heat in the R group as previously described. 23 This hypersensitivity seemed to be corrected with perineural dexamethasone but not with systemic dexamethasone (Fig. 3).…”
Section: Discussionmentioning
confidence: 95%
“…In the comparison study, Kolarczyk and Williams 5 found a statistically significant difference in PWL at 3 hours after the ropivacaine injection from baseline in the treated hind limb (baseline PWL = 9.04 T 2.64 vs 3-hour assessment = 5.5 T 2.34, n = 14 rats), but no evidence of heat hyperalgesia was detected at 5 hours, 7 hours, or at 2 weeks after the block. 5 The present analyses indicate only a short-lived period of hyperalgesia at the 240-minute time point and no other differences or trends to suggest hyperalgesia following the nerve block at any of the other time points assessed ( Table 2), illustrating that this slight degree of hypersensitivity is a transient phenomenon.…”
Section: Discussionmentioning
confidence: 44%
“…Authors suggest that this may be due to rebound pain [92,93]. Ultimately, TAP blocks may reduce or delay opioid use during the first 2-24 h postoperatively, after which patients may require greater opioid consumption to compensate for the transient hyperalgesia experienced during block regression [91].…”
Section: Transversus Abdominis Plane Blockmentioning
confidence: 97%